交代制勤務の看護師の生活時間構造と生活意識および疲労との関連 - 藤内 美保 (日本看護研究学会雑誌, 2004)
The relationship between daily time schedules and recognition for life and fatigue following night shift work by nurses was examined. Before night shifts, mean sleeping time after 5 p.m. was 2 h 36 min. Mean sleeping and napping time after night work was 4 h 48 min, despite fatigue. Mean time doing housework was 1 h 28 min for nurses with a daily work–night work pattern, with the majority of this time spent in cooking and childcare chores. Among nurses with a night work pattern, mean housework time was 2 h 10 min, time for social and cultural activities was 57 min, and leisure time with family a mere 7 min. In daily consciousness nurses felt various problems related to sleep. More than 80% of nurses felt stress due to irregularity of work, a lack of time to enjoy with family, disagreement of daily life rhythms, lack of hobbies or sports activities, limited opportunities to see friends, and lack of time for social and cultural activities. Less than 30% of nurses felt that they were in good health, or unworried about death due to overwork. 日勤－深夜勤務および深夜明けの２日間の看護師の生活時間の実態と交代制勤務の生活意識，疲労感や心身の健康状態を明らかにした。　 深夜勤務前の17時以降の睡眠・仮眠時間は平均２時間36分であった。深夜勤務終了後は疲労感が強いが，深夜勤務明けの睡眠時間は平均４時間48分と短い。家事的生活時間は日勤－深夜勤務では1時間28分，その大半は「毎日必要な家事」に費やしていた。深夜勤務明けの１日の家事時間は２時間10分であった。日勤－深夜勤務パターンの社会的文化的生活時間は27分で，そのうち「家族との団らん」は７分であった。　 生活意識では，睡眠に関する様々な問題を抱えていた。また「不規則な生活によるストレス」や「家族との団欒の不足」「趣味・スポーツ時間の不足」「友人・知人との交流機会の制限」と認識するものはすべての項目で８割を越えていた。また「健康である」や「過労死の不安はない」と自覚するものは両者とも３割に満たなかった。